2011
DOI: 10.1088/0957-0233/22/2/025104
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the particle spatial and velocity distributions in micro-abrasive jets

Abstract: Novel experimental techniques for obtaining the particle spatial distribution and the velocity distribution across a micro-abrasive jet were presented and tested. The spatial distribution of particles within the jet was found by using a direct particle capture technique, and was found to depend on the nozzle diameter, following either a Weibull or a piecewise Weibull distribution. In general, the jet was found to be more focused when more particles were present across the nozzle opening. It was demonstrated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…as a function of process and material variables [3][4][5][6][7][8][9]. For hard and brittle materials, the impact force of the abrasive particle causes localized cracks at the work surface.…”
Section: Introductionmentioning
confidence: 99%
“…as a function of process and material variables [3][4][5][6][7][8][9]. For hard and brittle materials, the impact force of the abrasive particle causes localized cracks at the work surface.…”
Section: Introductionmentioning
confidence: 99%
“…Burzynski and Papini [15] found βW =18 for 25 µm alumina particles blasted at 100 kPa. Since their results showed there is not a significant difference in βW for different particle sizes at a same condition, the same value (βW =18) is assumed to hold for 10 and 17 µm particles.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research found that it was impossible to machine cured PDMS using AJM at room temperature with 25 µm aluminum oxide particles impacting at approximately 140 m/s due to its ability to absorb the energy of the impacting particles [3]. Getu et al [3] were able to machine PDMS with 25 µm aluminum oxide particles at an impact velocity of approximately 140 m/s [9] using a cryogenic abrasive jet micromachining (CAJM) apparatus that cooled the surface region to approximately -150°C. Due to lack of cryogenic flow control, this experimental setup was only capable of blasting at the lowest temperature attainable while the surface was being flooded with liquid nitrogen.…”
Section: Motivationmentioning
confidence: 99%
“…By obtaining the surface profile of a shallow hole, the angle dependence of erosion could be ignored in Eq. 2-9 (Section 2.2.3) and the erosive power distribution of the jet could be inferred from a fitted polynomial of the surface, * @ * * @ * 9 * @ * (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) where V*(x*) and φ*(x*) are the particle velocities and mass flux distributions within the jet respectively, normalized by their values at the centre of the jet.…”
Section: Particle Mass Flux and Velocity Distributionmentioning
confidence: 99%